KARAKTERISTIK DIREKSI DAN PENGUNGKAPAN INFORMASI BERWAWASAN MASA DEPAN - Andreas Mardani; Ari Budi Kristanto (Dinamika Akuntansi Keuangan dan Perbankan, 2020)
The development ofcapital marketrequires a high need for informations. Company’s informationsare useful as an input for external parties in order to make a decision. This research aims to verify the influence of director characteristicstoward Forward-Looking Information (FLI) disclosure on Indonesian manufacturing companies. In this research, the board characteristics are consist of director’s over-confidence, gender and age. The population consist of all manufacturing companies which are registered on Bursa Efek Indonesia during the year of 2017-2018. The sample were taken using purposive sampling method, and obtained 60 companies. The level of FLI disclosure being measured by FLI score. The method of analysis used in this research was panel data regression analysis. The research result showed (1) the directors over-confidence has no significant effect on FLI disclosure, (2) the directors gender has no significant effect on FLI disclosure, (3) the directors age has a negative and significant effect on FLI disclosure in Indonesia manufacturing companies. Keywords: disclosure index; forward looking information disclosure; characteristic director; excessive confidence